Schule in Zeiten der Pandemie. Empfehlungen für die Gestaltung des Schuljahres 2020/21 - Expert*innenkommission der Friedrich-Ebert-Stiftung, D

Die drei zentralen Herausforderungen für den Bildungsbereich mit der Perspektive auf zukünftige Entwicklungen - Eickelmann, Birgit (Digitale Bildung nach Corona)

Nachhaltiger Digitalisierungsschub im Schulbereich und in der Lehrkräftebildung durch die Pandemie? – Schön wär’s - Eickelmann, Birgit

Strukturelle Rahmenbedingung der Digitalisierung im Schulbereich in NRW – neue Forschungsbefunde und mögliche Perspektiven für nachhaltig wirksame Entwicklungen - Eickelmann, Birgit (BildungsImpulseRuhr)

Lehrerbildung und Digitalisierung. Ein empirischer Blick auf der Grundlage der Studie ICILS 2018 - Gerick, Julia; Eickelmann, Birgit (Beiträge zur Lehrerbildung und Bildungsforschung. Digital?! Perspektiven der Digitalisierung für den Lehrerberuf und die Lehrerbildung)

Students’ computer literacy and the use of tablets in upper secondary schools - Eickelmann, Birgit; Drossel, Kerstin (Encyclopedia of Education and Information Technologies)

Computational thinking competences in countries from three different continents in the mirror of students' characteristics and school learning - Labusch, Amelie; Eickelmann, Birgit (Proceedings of International Conference on Computational Thinking Education 2020)

Modellschulen ‚Lernen mit digitalen Medien‘ in der Pandemie-Zeit – Gestaltungsansätze und Lessons Learnt - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie (Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Sozial- und migrationsbedingte Disparitäten im Bereich ‚Computational Thinking‘ von Schülerinnen und Schülern - Labusch, Amelie; Vennemann, Mario; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Kompetenzen im Bereich ‚Computational Thinking‘ von Schülerinnen und Schülern im internationalen Vergleich - Labusch, Amelie; Eickelmann, Birgit; Vahrenhold, Jan; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Die Nutzung digitaler Medien aus der Perspektive der Schülerinnen und Schüler - Vennemann, Mario; Labusch, Amelie; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Der Informatikunterricht aus Sicht schulischer Akteurinnen und Akteure – Analysen und Perspektiven - Vahrenhold, Jan; Vennemann, Mario; Labusch, Amelie; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Rolle des schulischen Ganztags für das Lernen mit digitalen Medien - Eickelmann, Birgit; Heldt, Melanie; Port, Sonja (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Konzeptionelle Verankerung digitaler Medien in schulisches Lernen und Lehren - Heldt, Melanie; Labusch, Amelie; Eickelmann, Birgit; Port, Sonja (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Modellschulen ‚Lernen mit digitalen Medien‘ in der Pandemie-Zeit – Gestaltungsansätze und Lessons Learnt - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie (SchulManagement. Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Schulleitung und Digitalisierung. Fünf Thesen - Eickelmann, Birgit (SchulManagement. Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Ergebnisse der wissenschaftlichen Begleitung der Evaluation des Projekts ‚Lernen mit digitalen Medien‘ an den Förderzentren Geistige Entwicklung/Körperliche und motorische Entwicklung in Schleswig-Holstein ergänzt um eine Vertiefungsuntersuchung im Kontext des Lernens mit digitalen Medien unter Pandemie-Bedingungen - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie

Ergebnisse der vertiefenden Untersuchung der Modellschulen ‚Lernen mit digitalen Medien‘ (Phase III) in Schleswig-Holstein mit Fokus auf der Gestaltung von Schule in der Zeit der Corona-Pandemie - Gerick, Julia; Eickelmann, Birgit

Ergebnisse der wissenschaftlichen Begleitung der Evaluation der dritten Phase des Projekts ‚Lernen mit digitalen Medien‘ mit dem Schwerpunkt auf digitalen Medien im Fachunterricht an Modellschulen in Schleswig-Holstein - Gerick, Julia; Eickelmann, Birgit

Re-Definition der digitalisierungsbezogenen Schulleitungsfunktionen in der Pandemie-Zeit. Plan BD #02 Leadership - Eickelmann, Birgit (Fachmagazin für Schule in der digitalen Welt)

Digitalisierungsbezogene Professionalisierung von Lehrpersonen. Befunde zu Aktivitäten, Gelegenheiten und schulischen Prioritäten aus ICILS 2013 und ICILS 2018 im Vergleich - Gerick, Julia; Eickelmann, Birgit; Vennemann, Mario (Journal für Schulentwicklung)

Fortbildung im digitalen Zeitalter (Journal für Schulentwicklung)

Der digitale Fußabdruck, Schatten oder Zwilling von Maschinen und Menschen - Engels, Gregor (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))

Annette-von-Droste-Hülshoff-Preis 2020 Michael Roes im Gespräch mit LWL-Direktor Matthias Löb und Prof. Dr. Norbert Otto Eke, - Eke, Norbert (www.literaturkommission.lwl.org/media/filer_public/cb/ad/cbad76c2-23ac-4cb1-ade3-883dcbd1bbf0/broschure_roes_210x210.pdf)

[zu:] Cristina Rossi: Sinn und Struktur. Zugänge zu den Collagen Herta Müllers. Würzburg: Königshausen & Neumann, 2019 - Eke, Norbert (Literaturwissenschaftliches Jahrbuch)

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Short-term metreleptin treatment of patients with anorexia nervosa: rapid on-set of beneficial cognitive, emotional, and behavioral effects - Milos, Gabriella; Antel, Jochen; Kaufmann, Lisa-Katrin; Barth, Nikolaus; Koller, Antonia; Tan, Susanne; Wiesing, Urban; Hinney, Anke; Libuda, Lars; Wabitsch, Martin; von Känel, Roland; Hebebrand, Johannes (Translational Psychiatry)
Abstract To examine the hypothesis that normalization of low circulating leptin levels in patients with anorexia nervosa ameliorates hyperactivity, three seriously ill females with hyperactivity were treated off-label with metreleptin (recombinant human leptin) for up to 14 days. Drive for activity, repetitive thoughts of food, inner restlessness, and weight phobia decreased in two patients. Surprisingly, depression improved rapidly in all patients. No serious adverse events occurred. Due to obvious limitations of uncontrolled case series, placebo-controlled clinical trials are mandatory to confirm the observed rapid onset of beneficial effects. Our findings suggest an important role of hypoleptinemia in the mental and behavioral phenotype of anorexia nervosa.

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study - Peters, Triinu; Nüllig, Lena; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Tegeler, Lisa; Amhaouach, Chaima; Libuda, Lars; Hinney, Anke; Hebebrand, Johannes (Frontiers in Genetics)

Shortest Paths in a Hybrid Network Model - Augustine, John; Hinnenthal, Kristian; Kuhn, Fabian; Scheideler, Christian; Schneider, Philipp (Proceedings of the 2020 ACM-SIAM Symposium on Discrete Algorithms, SODA 2020, Salt Lake City, UT, USA, January 5-8, 2020)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Chohan, Nadia; Reinhold, Jannik (ZWF, Zeitschrift für wirtschaftliche Fabrikplanung 115(7-8))
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.

Strategische Planung - Gausemeier, Jürgen; Eckelt, Daniel; Dülme, Christian (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbruegger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP (91))

Developing Strategies for Digital Transformation in SMEs with Maturity Models - Pierenkemper, Christoph; Gausemeier, Jürgen (Proceeding of the ISPIM Connects, 1. - 4. Mrz. 2020)

Pattern‐based development of digital platforms - Drewel, Marvin; Özcan, Leon; Koldewey, Christian; Gausemeier, Jürgen (Creativity and Innovation Management)

Mechanical and mathematical model of a caterpillar drive with a triangular contour for solving problems of vertical dynamics of a tracked vehicle - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Vestnik Mashinostroeniya)

Integrating Score Rendition in the MEI Garage - Rettinghaus, Klaus; Röwenstrunk, Daniel; Kepper, Johannes

Einfluss umgebungsbedingter Alterung auf das Werkstoffverhalten unverstärkter, kurzfaserverstärkter und gewebeverstärkter Thermoplaste - Hüttner , Matthias

Modellbasierte Beschreibung und Validierung der Glasfaserverkürzung im Spritzgießplastifizieraggregat mittels analytischer und und diskreter Ansätze - Heiderich, Gilmar

Evaluation of LLDPE and PLA Films Manufactured with High Speed - Bayazian, Hoda

Modellierung der Materialströmung auf gleichläufigen Doppelschneckenextrudern mit Hilfe der Performance Mapping Methode - Sporkmann, Frederik

Entwicklung einer Zylindertemperatureinstellungsregelung auf Basis von Fuzzy-Logik - Resonnek, Verena

Die Einstellung angehender Lehrkräfte zu Forschendem Lernen im Praxissemester und Referendariat - Homt, Martina; Bloh, Bea; Grosser, Christine (Forschendes Lernen in der Lehrer/innenbildung. Implikationen für Wissenschaft und Praxis)

Early changes in hepatic energy metabolism and lipid content in recent-onset type 1 and 2 diabetes mellitus - Kupriyanova, Yuliya; Zaharia, Oana Patricia; Bobrov, Pavel; Karusheva, Yanislava; Burkart, Volker; Szendroedi, Julia; Hwang, Jong-Hee; Roden, Michael; Roden, M.; Al-Hasani, H.; Burkart, V.; Buyken, Anette; et al. (Journal of Hepatology)

World trends in sugar-sweetened beverage and dietary sugar intakes in children and adolescents: a systematic review - Della Corte, Karen; Fife, Jessica; Gardner, Alexis; Murphy, Britta L; Kleis, Linda; Della Corte, Dennis; Schwingshackl, Lukas; LeCheminant, James D; Buyken, Anette (Nutrition Reviews)
Abstract Objective To provide a systematic overview of world dietary sugar and sugar-sweetened beverage (SSB) intake trends in children and adolescents. Data Sources Medline, Embase, and the Cochrane Central Register of Controlled Trials in the Cochrane Library were searched through January 2019 to identify longitudinal follow-up studies with time-trend data and repeated cross-sectional studies. Data Extraction Data from studies reporting ≥ 2 measurements (sugars, SSB, or sweets/candy) over ≥ 2 years and included ≥ 20 healthy, normal- or overweight children or adolescents aged 1–19 years. Data Analysis Data from 43 articles (n = 4 prospective cohort studies; n = 39 repeated cross-sectional studies) from 15 countries (n = 8 European countries plus Australia, Canada, China, South Korea, Mexico, Russia, and the United States) are presented narratively. According to the risk of bias in nonrandomized studies of interventions tool, 34 studies were judged to have a moderate risk of bias, and 5 to have a serious risk of bias. Conclusions Consumption among US children and adolescents increased substantially in the decades preceding 2000, followed by a faster and continued decline. As a whole, other international intake trends did not reveal drastic increases and decreases in SSB and dietary sugars; they tended to change only slightly across 3 decades.

Dietary Fibre Consensus from the International Carbohydrate Quality Consortium (ICQC) - Augustin, Livia S. A.; Aas, Anne-Marie; Astrup, Arnie; Atkinson, Fiona S.; Baer-Sinnott, Sara; Barclay, Alan W.; Brand-Miller, Jennie C.; Brighenti, Furio; Bullo, Monica; Buyken, Anette; Ceriello, Antonio; Ellis, Peter R.; et al. (Nutrients)
Dietary fibre is a generic term describing non-absorbed plant carbohydrates and small amounts of associated non-carbohydrate components. The main contributors of fibre to the diet are the cell walls of plant tissues, which are supramolecular polymer networks containing variable proportions of cellulose, hemicelluloses, pectic substances, and non-carbohydrate components, such as lignin. Other contributors of fibre are the intracellular storage oligosaccharides, such as fructans. A distinction needs to be made between intrinsic sources of dietary fibre and purified forms of fibre, given that the three-dimensional matrix of the plant cell wall confers benefits beyond fibre isolates. Movement through the digestive tract modifies the cell wall structure and may affect the interactions with the colonic microbes (e.g., small intestinally non-absorbed carbohydrates are broken down by bacteria to short-chain fatty acids, absorbed by colonocytes). These aspects, combined with the fibre associated components (e.g., micronutrients, polyphenols, phytosterols, and phytoestrogens), may contribute to the health outcomes seen with the consumption of dietary fibre. Therefore, where possible, processing should minimise the degradation of the plant cell wall structures to preserve some of its benefits. Food labelling should include dietary fibre values and distinguish between intrinsic and added fibre. Labelling may also help achieve the recommended intake of 14 g/1000 kcal/day.

Inflammatory mediators in the adipo-renal axis: leptin, adiponectin, and soluble ICAM-1 - Hua, Yifan; Herder, Christian; Kalhoff, Hermann; Buyken, Anette; Esche, Jonas; Krupp, Danika; Wudy, Stefan A.; Remer, Thomas (American Journal of Physiology-Renal Physiology)
A lower 24-h urine pH (24h-pH), i.e., a higher renal excretion of free protons, at a given acid load to the body, denotes a reduction in the kidney’s capacity for net acid excretion (NAE). There is increasing evidence, not only for patients with type 2 diabetes but also for healthy individuals, that higher body fatness or waist circumference (WC) has a negative impact on renal function to excrete acids (NAE). We hypothesized that adiposity-related inflammation molecules might mediate this relation between adiposity and renal acid excretion function. Twelve biomarkers of inflammation were measured in fasting blood samples from 162 adult participants (18–25 yr old) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had undergone anthropometric measurements and collected 24-h urine samples. Both Baron and Kenny’s (B&K’s) steps to test mediation and causal mediation analysis were conducted to examine the potential mediatory roles of biomarkers of inflammation in the WC-24-h pH relationship after strictly controlling for laboratory-measured NAE. In B&K’s mediation analysis, leptin, soluble intercellular adhesion molecule 1 (sICAM-1), and adiponectin significantly associated with the outcome 24-h pH and attenuated the WC-pH relation. In agreement herewith, causal mediation analysis estimated the “natural indirect effects” of WC on 24-h pH via leptin ( P = 0.01) and adiponectin ( P = 0.03) to be significant, with a trend for sICAM-1 ( P = 0.09). The calculated proportions mediated by leptin, adiponectin, and sICAM-1 were 64%, 23%, and 12%, respectively. Both mediation analyses identified an inflammatory cytokine (leptin) and an anti-inflammatory cytokine (adiponectin) along with sICAM-1 as being potentially involved in mediating adiposity-related influences on renal acid excretion capacity.

Early life factors and their relevance to intima-media thickness of the common carotid artery in early adulthood - Nyasordzi, Juliana; Penczynski, Katharina; Remer, Thomas; Buyken, Anette (PLOS ONE)

Reply to Khan et al. - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)

Sugar intake among German adolescents: trends from 1990 to 2016 based on biomarker excretion in 24-h urine samples - Perrar, Ines; Gray, Nicola; Kuhnle, Gunter G.; Remer, Thomas; Buyken, Anette; Alexy, Ute (British Journal of Nutrition)
Abstract Trend analyses based on dietary records suggest decreases in the intakes of total sugar (TS), added and free sugar since 2005 among children and adolescents in Germany. In terms of age trends, TS intake decreased with increasing age. However, self-reported sugar intake in epidemiological studies is criticised, as it may be prone to bias due to selective underreporting. Furthermore, adolescents are more susceptible to underreporting than children. We thus analysed time and age trends in urinary fructose excretion (FE), sucrose excretion (SE) and the sum of both (FE + SE) as biomarkers for sugar intake among 8·5–16·5-year-old adolescents. Urinary sugar excretion was measured by UPLC-MS/MS in 997 24-h urine samples collected from 239 boys and 253 girls participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study cohort between 1990 and 2016. Time and age trends of log-transformed FE, SE and FE + SE were analysed using polynomial mixed-effects regression models. Between 1990 and 2016, FE as well as FE + SE decreased (linear time trend: P = 0·0272 and P < 0·0001, respectively). A minor increase in excretion during adolescence was confined to FE (linear age trend: P = 0·0017). The present 24-h excretion measurements support a previously reported dietary record-based decline in sugar intake since 2005. However, the previously seen dietary record-based decrease in TS from childhood to late adolescence was not confirmed by our biomarker analysis, suggesting a constant sugar intake for the period of adolescence.

The Relationship between Glycemic Index and Health - Brand-Miller, Jennie; Buyken, Anette (Nutrients)
There is no question that elevated postprandial glycemia is a significant driver of common chronic diseases globally [...]